Sprint skating profile of competitive male bandy players: determination of positional differences and playing level - van den Tillaar, Roland; Pojskic, Haris; Andersson, Håkan (Frontiers in Physiology, 2023)
This study compares sprint skating profile characteristics of the different playing positions of junior and senior bandy players. In total, 111 male national-level bandy players (age: 20.7 ± 5.0 years, height: 1.80±0.05 m, body mass: 76.4±.4 kg, training experience: 13.8±5.0 yrs.) were tested on their sprint skating profile over 80 m. The main findings were that no differences between positions were found in sprint skating performance, but that elite players were in general heavier (p<0.05) than junior players (80.0±7.1 vs. 73.1±8.1 kg), they could accelerate faster, and they reached a higher velocity (10.83±0.37 vs. 10.24±0.42 m/s) earlier over 80m than the junior players. There was no difference between sprint skating performance in bandy players between positions but playing level influences acceleration capacity, with higher acceleration (2.96±0.22 vs. 2.81±0.28 m/s2) at an elite level when compared with junior level. This implies that junior level players should spend more time in power and sprint training to meet the specific demands of playing at a higher, elite level.